Extension of Consumer Brand Engagement Framework: Indonesian Smartphone Brands Consumers - Ardiyanto , Faizal; Kusumadewi, Hermala (KnE Social Sciences, 2022)
This research identifies evidence regarding the nexus between the antecedents of CBE dimensions and consequences on smartphone brands in Indonesia. Data were collected through an online questionnaire targeted at a total of 1251 smartphone users/consumers in Indonesia. AMOS SEM was used in processing the statistical tests of this research. Convergent validity and composite reliability were also used to check the questionnaire items. The authors found that consumer involvement and self-expressive brand affect all the CBE dimensions (COG, AFF, ACT) while consumer participation only affects one CBE dimension (COG). Subsequently, CBE dimensions affect brand usage intent and self-brand connection. Therefore, this study contributes to the body of work in consumer brand engagement literature. Keywords: consumer brand engagement, consumer involvement, consumer participation, self-expressive brand, brand usage intent, and self-brand connection